2003
DOI: 10.1034/j.1600-0560.2003.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mismatch repair proteins in sebaceous gland tumors

Abstract: Background: Sebaceous gland neoplasms are rare tumors that are associated with visceral malignancies in patients with Muir^Torre syndrome (MTS).The majority of the MTS-associated tumors reveal mutations in DNA mismatch repair (MMR) genes (most often hMSH-2 and hMLH-1) and microsatellite instability.The sebaceous gland lesions in patients with MTS can often precede or occur concurrently with the visceral neoplasms.The early recognition of those lesions and their differentiation from sporadic sebaceous gland tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 22 publications
0
27
3
1
Order By: Relevance
“…For sporadic sebaceous lesions, these data are within the range reported by the literature, which varies from 0% 19 to 23%. 18,20 In contrast, the percentage of MMR 2 sebaceous lesions associated with visceral tumors was significantly lower than previously reported. 19,20 This discrepancy could be related to differences in the way that cases were recruited.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…For sporadic sebaceous lesions, these data are within the range reported by the literature, which varies from 0% 19 to 23%. 18,20 In contrast, the percentage of MMR 2 sebaceous lesions associated with visceral tumors was significantly lower than previously reported. 19,20 This discrepancy could be related to differences in the way that cases were recruited.…”
Section: Discussioncontrasting
confidence: 75%
“…18,20 In contrast, the percentage of MMR 2 sebaceous lesions associated with visceral tumors was significantly lower than previously reported. 19,20 This discrepancy could be related to differences in the way that cases were recruited. In particular, in this study, patients were not selected according to age or family history.…”
Section: Discussioncontrasting
confidence: 75%
“…Although the possibility that this patient has MTS cannot be totally refuted (some patients with MTS develop extracutaneous tumors many years after the diagnosis of a cutaneous lesion), this case may be equally regarded as sporadic; loss of MMR protein has been reported in sporadic cutaneous sebaceous neoplasms. 15 Interestingly, this single MLH1-deficient tumor was situated on the chest wall. A recent study examining the association of sebaceous tumor type and site with MMR status showed that sebaceous neoplasms that occur outside of the neck and neck area are very likely to be MMR deficient.…”
Section: Discussionmentioning
confidence: 98%
“…A módszer szenzitív, adott MMR-fehérjére specifi kus és könnyen reprodukálható. Hátránya, hogy a negatív eredmény nem zárja ki az MMR-génmutációt [28,29,30]. Másodvonalbeli tesztként az MSI-elemzés alkalmazható.…”
Section: áBraunclassified